Upaya Guru Pendidikan Agama Islam (PAI) dalam Meningkatkan Kedisiplinan Siswa di SMAN 3 Kota Bima - Rizka Amanda Khatimah; Taman Firdaus; Irwan Irwan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to describe the factors contributing to students’ low level of discipline and to explain the efforts made by Islamic Religious Education (PAI) teachers to improve student discipline at SMAN 3 Kota Bima. The study employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that students’ low discipline is influenced by both internal and external factors. The internal factors include low self-awareness, negative habits carried over from previous levels of education, and low learning motivation, particularly in Islamic Religious Education subjects. Meanwhile, the external factors include the influence of peer groups, limited parental supervision, and the use of gadgets and social media. The efforts made by PAI teachers to improve student discipline include several strategies: providing exemplary behavior, habituating students to routine religious activities such as Dhuha prayer and congregational Dzuhur prayer, providing motivation and advice based on Qur’anic values, consistently implementing reward and punishment, and applying personal and collaborative approaches involving homeroom teachers, guidance and counseling teachers, and parents. This study concludes that PAI teachers play a highly strategic role in shaping students’ disciplined character through a holistic approach that integrates religious values, positive habituation, and multi-party collaboration.